2011
DOI: 10.1109/tbme.2010.2086456
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in Noncontact, Multiparameter Physiological Measurements Using a Webcam

Abstract: Abstract-We present a simple, low-cost method for measuring multiple physiological parameters using a basic webcam. By applying independent component analysis on the color channels in video recordings, we extracted the blood volume pulse from the facial regions. Heart rate (HR), respiratory rate, and HR variability (HRV, an index for cardiac autonomic activity) were subsequently quantified and compared to corresponding measurements using Food and Drug Administration-approved sensors. High degrees of agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
901
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,224 publications
(921 citation statements)
references
References 22 publications
(22 reference statements)
8
901
3
9
Order By: Relevance
“…Poh et al [1] show that heart rate, breath rate and heart rate variability can be determined by a laptop's built-in video camera with great accuracy. Scully et al [2] use the video of a subject's finger resting on a mobile phone's camera lens to extract heart rate, heart rate variability, breathing rate and blood oxygen saturation.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…Poh et al [1] show that heart rate, breath rate and heart rate variability can be determined by a laptop's built-in video camera with great accuracy. Scully et al [2] use the video of a subject's finger resting on a mobile phone's camera lens to extract heart rate, heart rate variability, breathing rate and blood oxygen saturation.…”
Section: Relation To Prior Workmentioning
confidence: 99%
“…Facial video recording using the smartphone camera is a novel method of detecting a pulsatile facial photoplethysmographic signal without physical contact,18, 19, 20 with the potential for distant screening. A small proof‐of‐concept study supported the feasibility of such a contact‐free method for AF detection,19 but the performance of facial photoplethysmography for the detection of AF in a prospective study has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early experiments have confirmed the viability of this technique (Poh et al, 2010;Farley et al, 2011;Poh et al, 2011). …”
Section: Absorption Coefficientmentioning
confidence: 87%